Monitoring energy audit for energy savings using non cost technique at electronics company - M. N., Mohd Foudzi; Mohd Yusof, Taib; A. S., Arnizam Shah; A. R., Yusoff (Penerbit UMP, 2021)
Energy is essential element for economical growth in industry and it measures directly the standard of living for a country. The economical growth and energy demand in the modern society need to be reduced the energy consumption. In this paper, energy consumption was monitored and audited for an electronic company in Malaysia. The energy consumption was analysed based on electrical bill and then the power consumption has been verified based on energy audit process using power analyser for this electronic company. It is monitored that the energy audit for the whole company and point out the possiblity of non cost energy saving technique. From 10 locations analyses, 3 locations are main soursces contribite to high energy consumption. There are compressor room, busbar 15 and busbar 16 relates to chiller room that supply the air conditioning system in the company. The energy audit can provide the non cost suitable technique for energy savings and profit improvement in this electronic company.